Determinan Profitabilitas Berkelanjutan Pada Industri Perbankan Dengan Value Added Human Capital Sebagai Pemoderasi - Ari Kristanto Ari; Endang Etty Merawati (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This study aims to examine how to influence Corporate Social Responsibility and managerial ownership with Value Added Human Capital as a moderating variable. The population used in this study is the banking industry, with a sampling technique using purposive sampling. The sample used in this study was 276 test units, consisting of 46 companies for 6 years of research. The research method used is quantitative methods with secondary documentation data collection techniques originating from the Indonesia Stock Exchange which are processed using moderate regression analysis equations. The results show that Corporate Social Responsibility has a significant effect on Profitability, Managerial Ownership has a significant influence on Profitability, Value Added Human Capital can moderate the influence of Corporate Social Responsibility and Ownership on profitability. Assets).